Linear-quadratic and norm-bounded combined differential game guidance scheme with obstacle avoidance for attacking defended aircraft in three-player engagement - Xintao Wang; Ming Yang; Songyan Wang; Mingzhe Hou; Tao Chao (Defence Technology)
A differential game guidance scheme with obstacle avoidance, based on the formulation of a combined linear quadratic and norm-bounded differential game, is designed for a three-player engagement scenario, which includes a pursuer, an interceptor, and an evader. The confrontation between the players is divided into four phases (P1–P4) by introducing the switching time, and proposing different guidance strategies according to the phase where the static obstacle is located: the linear quadratic game method is employed to devise the guidance scheme for the energy optimization when the obstacle is located in the P1 and P3 stages; the norm-bounded differential game guidance strategy is presented to satisfy the acceleration constraint under the circumstance that the obstacle is located in the P2 and P4 phases. Furthermore, the radii of the static obstacle and the interceptor are taken as the design parameters to derive the combined guidance strategy through the dead-zone function, which guarantees that the pursuer avoids the static obstacle, and the interceptor, and attacks the evader. Finally, the nonlinear numerical simulations verify the performance of the game guidance strategy.